An ecological approach: a viable option for aquaculture industry in Malaysia - Md. Yusoff, Fatimah (2003)
Aquaculture sector in Malaysia is poised to playa major role to compensate for the declining capture fisheries, and is expected to emerge as one of the major agricultural contributors to the national economy. The industry is anticipated to increase the production to 600,000 mt, generating returns up to US$2.63 billion by 2010. This is a significant increase of approximately 360% in production compared to the current production of 167,894 mt valued at US$255.34 million. Aquaculture involves utilization of natural resources such as clean water, vast tracks of land, feed materials and fertilizers to produce desirable products with simultaneous production of organic and chemical wastes. Thus, the successful development of this sector is dependent on the nation's ability to utilize its resources efficiently and sustain its growth without adversely affecting the aquatic environment. At present, most aquaculture practices in Malaysia generate adverse impacts on aquatic environment, the very resource that determine the sUccess and the sustainability of the aquaculture industry. Wetland habitats such as mangroves, estuaries, sea-grass beds, coral reefs and mudflats are particularly vulnerable, especially when the impacts exceeded the ecosystem's resilience and carrying capacity. However, carrying capacity in various ecosystems is poorly known and thus the tendency to exceed the upper limit seems to be common in most environments. Adverse impacts associated with aquaculture, especially the intensive systems, include habitat destruction, discharge of effluents with high organic contents, contamination of the aquatic environment with chemicals, eutrophication, disease outbreak, effects of escaped- exotic species and decrease in biodiversity.